2013
DOI: 10.3109/10253890.2013.807243
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stress on core and peripheral body temperature in humans

Abstract: Even though there are indications that stress influences body temperature in humans, no study has systematically investigated the effects of stress on core and peripheral body temperature. The present study therefore aimed to investigate the effects of acute psychosocial stress on body temperature using different readout measurements. In two independent studies, male and female participants were exposed to a standardized laboratory stress task (the Trier Social Stress Test, TSST) or a non-stressful control tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(117 citation statements)
references
References 46 publications
3
104
1
3
Order By: Relevance
“…The present findings are perhaps more consistent with a general fear / anxiety response to the body-threat (see Vinkers et al, 2013), rather than reflecting shifts in limb ownership.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The present findings are perhaps more consistent with a general fear / anxiety response to the body-threat (see Vinkers et al, 2013), rather than reflecting shifts in limb ownership.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, previous research has argued that drops in body / finger temperature can reflect a psychophysiological anxiety response (Vinkers, et al, 2013), and this has been shown for non-clinical samples in relation to body illusions (full body illusions: Salomon et al, 2013; the RHI: Moseley et al, 2008;Kammers et al, 2011;Thakkar et al, 2011: though see also Hohwy & Paton, 2010;Paton et al, 2012 for failures to replicate). Therefore, finger temperature was measured as an additional objective index of threat-related anxiety, via a separate channel on the same MP36R unit described above.…”
Section: Finger / Body Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Outra forma de detectar a presença do estresse é a partir do monitoramento de sinais biológicos. A detecção pode ser realizada por sensores capazes de medir variações dos sinais de resposta galvânica da pele (GSR) [4], temperatura da superfície do corpo [5], eletrocardiografia (ECG) [6], eletromiografia (EMG) [7], eletroencefalografia (EEG), frequência cardíaca, pressão arterial, taxa de respiração e outros [8]. Devido a necessidade do monitoramento dos sinais do organismo de forma contínua e sem prejudicar a rotina do usuário, os dispositivos vestíveis tem ganhado espaço no mercado de healthcare.…”
Section: Introductionunclassified
“…Since conductive gel is used at the fingertips, the connection of SKT changes. For instance, the participants in [223] were exposed to a stressinducing activity while their skin temperature was being simultaneously collected at several body locations. The results showed that, due to stress, temperature significantly increased on the neck over time compared to the control condition, while it significantly decreased on the fingertip.…”
Section: Ppg Signalmentioning
confidence: 99%